Unveiling the prediction model and mechanism of the collapse of bank slope in the lancangjiang area - An, Xiaofan; Guo, Shuangfeng; Ju, Guanghong; Bai, He; Hu, Hua; Wang, Zhe; Hu, Yanbo (Frontiers in Earth Science, 2024)
This study takes the bank collapse at the left bank of Badi Township of the Lidi Hydropower Station in the Lancang Area as an example. To address the lack of in-depth research on the prediction model and mechanisms of bank collapse, this study conducts field drilling surveys, investigates influencing factors, analyzes causal mechanisms, and proposes prediction methods based on the geological survey data of bank collapse in the reservoir area. The study explores the stratigraphic lithology, determines the key parameters for bank collapse prediction, and studies the failure modes and bank collapse mechanisms. It also proposes the finite element method of bank collapse to predict the width and elevation of bank collapse and provides the influence on the surrounding environment. The results show that the collapsed bank on the left bank of Badi Township is a high and steep soil-like slope, and forms the collapse and retreat type of failure mode after impoundment. The Kachukin method, the bank slope structure method, and the proposed finite element method are used to predict the width and elevation of the collapsed bank. The results indicate that the Kachujin method predicts a larger range of bank collapses and is biased towards safety. In contrast, the prediction ranges of the bank slope structure method and the finite element method are close. The bank collapse position is located in the middle and rear of the residential houses in Badi Township, which is consistent with the on-site investigation and has strong reliability. The predicted width of the bank collapse is about 34 m and the elevation is about 1,845 m. The research results can be directly applied to preventing and controlling bank collapse and have powerful practical application value.